Importance of Conducting Cyber Security Awareness Sessions among Undergraduate Students - Arshiya Subhani; Iftikhar Alam Khan; Usman Ahmad (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: In this digital era, a person’s day begins with digital devices such as digital watches or smartphones. Cyber security is one of the major concerns in this era. Every device is connected, and hence, it is one of the reasons for most of the data security issues. The aim of this paper is to find out if it is necessary to conduct cybersecurity awareness sessions among students of different fields of study.Methodology: A survey was conducted using the questionnaires and respondents are students from three different fields of study, Creative Computing, Business and Management and Psychology at BSU Academic Center, RAK, UAE. For current research, the Google form was used to conduct a survey and shared via WhatsApp group messages to all students. There was a total of 141 respondents. The insights from the survey were conducted for the student’s age group of 17- 21.Findings: The findings show a significant difference between the responses of three fields of study. The students of Creative computing are well aware of cyber security terminologies compared to students from other fields of study.Implications/Novel Contribution: The students can be guided with appropriate cyber laws to understand the importance of data security. In the future, cyber security awareness could be created among students by conducting seminars and workshops..